THE RACE ROOTS OF THE UZBEK POPULATION - Tagayalieva, N.A.; Yakubova, R.A.; Baratov, Q.R.; Rahmonova, G.G. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
In this work the biomedical significance of the concept of race is addressed; and in this regard, an analysis of the available scientific literature on the genetic determinants of the racial / ethnic identity of the Uzbek population, namely, the comparative analysis of distribution of haploid and autosomal markers among nowadays living nationalities of the Central Asia was carried out. The Uzbek population is represented by admixture of Caucasian, East Asian and partially South Asian genes as a result of migration flows from the coasts of the Eurasia to its center. For Uzbeks maximum genetic diversity was demonstrated among other Central Asian populations under study. The ethnic groups of Karakalpaks, Tajiks, Turkmens, Kazakhs was found to be the closest ones to the Uzbek one. The Uzbek settlements located out of the territory of Uzbekistan retain their specific genetic diversity.